Association of Wheat Allergy and Coeliac Disease through Pediatric and Adult Age: A Review of Literature - Panasiti, Ilenia; Costa, Stefano; Caminiti, Lucia; Crisafulli, Giuseppe; Pajno, Giovanni B.; Pellegrino, Salvatore; Testagrossa, Barbara; Acri, Giuseppe (Current Nutrition & Food Science, 2021)
In recent years, the prevalence of large spectrum of gluten-related disorders (GRDs) has increased. Gluten is one of the most widely distributed components of food in both industrialized and developing countries. The main structural protein complex of wheat and its proteins are classified into albumins, salt-soluble globulins, and insoluble prolamins (gliadins and glutenins). Gluten is also included in other cereals, including rye and barley. GRDs can be classified, based on their pathogenic mechanism, into (i) Autoimmune disorders, (ii) Allergic disorders, (iii) No autoimmune, not allergic disorders. Coeliac disease (CD) is an autoimmune disorder that occurs in genetically predisposed individuals who develop an immune reaction to gluten. It affects about 1% of people in most populations. The disease primarily interests the small intestine, but it is characterized by a wide range of clinical presentations, with both intestinal and extra-intestinal symptoms. Wheat allergy (WA) is an adverse immunologic reaction to wheat proteins. In the large field of WA a further classification can be made, distinguishing IgE-dependent WA, triggered by ingestion, inhalation or cutaneous and/or mucosal contact of wheat, and IgE-non-dependent WA. Its prevalence varies depending on the age and region, from 0.4% to 4%. Urticaria and/or angioedema, and anaphylaxis with or without exercise as a trigger, appear typically during childhood, asthma and/or rhinitis (Baker’s asthma) are more common during adulthood. Non-coeliac gluten sensitivity (NCGS) is a condition in which gluten ingestion leads to one or more of a variety of immunological, morphological or symptomatic (both gastrointestinal or extra gastrointestinal) manifestations in people in whom CD has been excluded. It is supposed it’s due to an activated innate immune response.
Keywords: coeliac disease